GPS, fingerprint and QR-code based attendance system - Lim, Guo Hong (2019)
GPS, Fingerprint and QR-Code based Attendance System is a combination of GPS module, Fingerprint and QR-code features mobile application which use to take the students’ attendances in class. The system is developed to prevent students cheating on attendances, reduce the time consuming on taking attendances and reduce the workload of the lecturer when calculating the students’ attendances. The objective of this project is to study the existing system and compare the existing system with the proposed system. Besides, this project is to design and develop a system combining with GPS module for tracking the students’ attendances when check-in. The last objective of this project is to test the application to ensure that there is free of bugs and errors. This system is only available for Android devices and only for taking students’ attendance. The system has 2 users which are student and lecturer. For the first time users, they require to register first before using it. The methodology of this project of “GPS, Fingerprint and QR-Code Based Attendance System” is using Agile development model. This is because Agile development model can make any changes of the requirement at any time even late in the development. Besides, it reduces the time constraint of development by dividing a big task to the several small tasks. The “GPS, Fingerprint and QR-Code Based Attendance System” have several functions which Fingerprint verification on the login site, QR-Code scanning for students’ check-in, GPS navigation for lecturer to track the student location when students’ check-in and generating students’ attendance report. This system has been tested by using User Acceptance Test (UAT) by both users which are student and lecturer. The tested result shows that the system is working well and free of bugs and fulfilled the user requirements.